TIMM : the International Male Magazine. (London : Frankel Publications Ltd., 1968)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweemaandelijks
Redactie : 77 New Bond Street, London W1
Engels
Periodiek